Industrial chemical thesaurus - Ash, Michael; Ash, Irene (Synapse Information Resources, 2009)
Contains trade name chemicals linked to chemicals with contact information for manufacturers that produce these chemicals under their trade name or generic names.
Keywords: Chemistry -- Handbooks, manuals, etc.; Chemical engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books